Comments on dpa calculation methods for ion beam driven simulation irradiations - Bratchenko, M.I.; Bryk, V.V.; Dyuldya, S.V.; Kalchenko, A.S.; Lazarev, N.P.; Voyevodin, V.N. (Вопросы атомной науки и техники, 2013)
The methodology of application of computer simulation technique to the NSC KIPT advanced simulation studies of radiation materials science at charged particles accelerators is considered with due account of the conformance of simulation methods and algorithms to the working standards of nuclear engineering. The ambiguities of dpa calculations by means of the SRIM code are demonstrated and analyzed using complementary simulations by means of the RaT Monte-Carlo code. The refined guideline of the SRIM dpa calculations is presented. Методологія застосування методів комп’ютерного моделювання до імітаційних експериментів радіаційного матеріалознавства на прискорювачах заряджених частинок, що розвиваються у ННЦ ХФТІ, розглянута з особливою увагою до відповідності методів й алгоритмів моделювання до діючих стандартів атомної науки і техніки. Продемонстровані неоднозначності у розрахунках з.н.а. засобами коду SRIM. Їх аналіз проведений шляхом додаткового моделювання Монте-Карло-кодом RaT. Представлена вдосконалена методика розрахунків з.н.а. пакетом SRIM. Методология применения методов компьютерного моделирования к развиваемым в ННЦ ХФТИ имитационным экспериментам радиационного материаловедения на ускорителях заряженных частиц рассмотрена с особым вниманием к соответствию методов и алгоритмов моделирования действующим стандартам атомной науки и техники. Продемонстрированы неоднозначности в расчетах с.н.а. средствами кода SRIM. Проведен их анализ путем дополнительного моделирования Монте-Карло-кодом RaT. Представлена усовершенствованная методика расчетов с.н.а. пакетом SRIM.